Methodology for the Review and Update of Nutrient Criteria Underpinning Front-of-Pack Labeling: Application to the Glycemic Index Symbol - Starck, Carlene; Blumfield, Michelle; Abbott, Kylie; Cassettari, Tim; Wright, Jutta; Duve, Emily; Barclay, Alan W.; Fayet-Moore, Flavia (Frontiers in Nutrition, 2022)
Background. Nutrient criteria underlying front-of-pack food labelling programs can play an important role in improving dietary intakes. Currently, no methodology for the development or update of nutrient criteria has been published, nor the methods used by food regulatory bodies. The scientific publication of methodology outlining the development and update of nutrient criteria underpinning front-of-pack food labelling programs highlighting healthier food choices is needed. Objectives. To develop and provide a globally applicable and transparent methodology for researchers to follow when reviewing existing or developing new nutrient criteria for front-of-pack labelling. Methods. The Nutrient Criteria Methodology involved five phases: Phase I, the development of guiding principles; Phase II, collection of information for subsequent phases, including a pre-scope of the literature and selection of food composition database(s) for modelling; Phase III, literature review of all possible nutrients relevant to the nutrient criteria; Phase IV, database modelling to set quantitative limits for each selected nutrient; Phase V, assessment of the criteria against an established nutritional quality assessment tool. As an example, the methodology was applied to the update of the GI Symbol Product Eligibility and Nutrient Criteria (PENC). Results. A comprehensive and replicable methodology, based on best practice protocols and ensuring both scientific credibility and practicality of use by industry, was developed. Application of the five phases of the methodology to the GI Symbol PENC highlighted the ability of the methodology to uncover nutritional measures currently missing in many nutrient criteria for front-of-pack food labelling programs and other national food labelling systems, such as glycemic load and the unsaturated to saturated fat ratio. Foods achieving the PENC had a higher Health Star Rating than foods not achieving the PENC. Conclusion. Our Nutrient Criteria Methodology can be applied to the development and update of global nutrient criteria underpinning front-of-pack food labelling programs . Further research into the implementation of additional nutritional measures found to be important for human health is recommended, with the goal of the prevention of diet-related disease.